(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
Given the forthcoming need for the construction of a repository for low and intermediate radioactive level waste in the Republic of Croatia, this paper proposes a repository design which is, from a geotechnical point of view, simple, practical and safe, and significantly improved considering current conceptual designs. Existing low and intermediate radioactive level waste repositories are mostly vault-type, near-surface constructions with some kind of covering (top) system of protective layers. However, most of these repositories do not have a bottom protective system, apart from concrete flooring (base). The reasons for such designs include the presumed longevity of the waste packages (containers), which are mostly reinforced concrete and/or steel containers. Considering that the concrete is a material which will, under certain conditions, deteriorate (e.g. dissolution of the cement matrix), and so potentially release radionuclides to the environment, it is essential to design the repository in such a manner that all forms of early release of radionuclides are prevented. The improved conceptual design of low and intermediate radioactive level waste repository presented in this paper is intended to provide an improved containment of radionuclides from waste and ensure the long term safety of the repository. This paper is the first in a series which will cover the basic design of the repository, systems of protective layers and preliminary slope stability analyses.